2019
DOI: 10.1016/j.neuroimage.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A framework for linking resting-state chronnectome/genome features in schizophrenia: A pilot study

Abstract: Multimodal, imaging-genomics techniques offer a platform for understanding genetic influences on brain abnormalities in psychiatric disorders. Such approaches utilize the information available from both imaging and genomics data and identify their association. Particularly for complex disorders such as schizophrenia, the relationship between imaging and genomic features may be better understood by incorporating additional information provided by advanced multimodal modeling. In this study, we propose a novel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 93 publications
3
16
0
Order By: Relevance
“…The evolving motifs fluidly move through transient states of connectivity that resemble familiar formations obtained from the basic time-blind clustering into single transiently realized connectivity patterns ( Figure 2 ). Consistent with published results [35, 49, 53, 54, 57] on occupancy rates of time-blind SNAPdFNC states, we find here that: strongly modularized and hyperconnected patterns feature more prominently in EVOdFNCs with greater representational importance in controls (1, 5, 7 and 8) and in EVOdFNCs whose representational importance in controls is not statistically distinguishable from that in patients (4, 6, 9); weak connectivity and modularized negative DMN-to-other (DMNneg) patterns (2, 3) feature more prominently in EVOdFNCs with significantly higher representational importance in patients. A novel modularized pattern of functional organization, not seen in time-blind SNAPdFNC states, appears in EVOdFNC 10, which features a persistent stretch of strong modularized negative SM-VIS/CC/DMN connectivity.…”
Section: Resultssupporting
confidence: 93%
“…The evolving motifs fluidly move through transient states of connectivity that resemble familiar formations obtained from the basic time-blind clustering into single transiently realized connectivity patterns ( Figure 2 ). Consistent with published results [35, 49, 53, 54, 57] on occupancy rates of time-blind SNAPdFNC states, we find here that: strongly modularized and hyperconnected patterns feature more prominently in EVOdFNCs with greater representational importance in controls (1, 5, 7 and 8) and in EVOdFNCs whose representational importance in controls is not statistically distinguishable from that in patients (4, 6, 9); weak connectivity and modularized negative DMN-to-other (DMNneg) patterns (2, 3) feature more prominently in EVOdFNCs with significantly higher representational importance in patients. A novel modularized pattern of functional organization, not seen in time-blind SNAPdFNC states, appears in EVOdFNC 10, which features a persistent stretch of strong modularized negative SM-VIS/CC/DMN connectivity.…”
Section: Resultssupporting
confidence: 93%
“…Patients with bipolar disorder and major depression expressed TVC abnormalities mainly in executive (Rashid et al, 2014; Du et al, 2017), amygdala/salience (Qiu et al, 2018; Zhi et al, 2018), and salience/executive regions (Mokhtari et al, 2018a,b). Schizophrenia patients showed a complex pattern of decreased and increased TVC mainly in the DMN (Sakoglu et al, 2010; Abrol et al, 2017), and in frontal, parietal, auditory (Damaraju et al, 2014; Rashid et al, 2014; Du et al, 2017, 2018; Sun et al, 2018), visual (Fu et al, 2018; Rashid et al, 2018b; Sun et al, 2018), and thalamic areas (Damaraju et al, 2014; Rashid et al, 2014, 2018b; Du et al, 2018). Schizophrenia patients spent less time and made fewer transitions between states characterized by weak correlations between the thalami and sense-related brain regions (Damaraju et al, 2014).…”
Section: Application Of Time-varying Fc Techniques To Psychiatric Andmentioning
confidence: 99%
“…Our study revealed a significant coupling between the expression pattern of mitochondria-related genes and the intrinsic chronnectome pattern, with high expression dominantly located in the bi-active hubs (medial/lateral prefrontal and parietal cortices) that exhibit a high level of dynamic features. Consistently, the occupancy rate in the dynamic connectivity state linking most of these regions is associated with a single nucleotide polymorphism component with top related genes associated with metabolism 44 . These regions are essential to mediate various complex cognitive functions 45 and are phylogenetically late developing, with a disproportionate enlargement during evolution 46 .…”
Section: Discussionmentioning
confidence: 65%